Language and diversity in Catalonia school: a glocal project - Vallcorba Cot, Josep (Avances en Supervisión Educativa, 2010)
The matter of linguistic variety in Catalonia school system has already and undoubtedly acquired some experience and strength and it is a pedagogical heritage for many students at present and former students who have benefited themselves from this system and also for many teachers at primary and secondary education levels who have performed really well even in, at times, very hard conditions.